KONSTRUKSI IDEOLOGI GENDER PADA MAJALAH WANITA (ANALISIS WACANA KRITIS MAJALAH UMMI) - Ummy Hanifah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2011)
UMMI’s magazine is one of Islamic magazine which is segmented for women andhas positioned their self as da’wa media. The problems of this research are how UMMIconstruct the gender rules to their readers and how that rules are presented in this media.The approach that used in this research is the theory of content of media from Shoemakerand Reese. There are many factors that influence of content of media such as individualfactors, media’s rutinity, organizational factor, extra media and ideologi. Method beingused in this research was qualitative-descriptive along with critical discourse analysis fromNorman Fairclough. The result showed that UMMI successfully construct double rules totheir readers.